Peran Teknologi Informasi, Partisipasi Anggaran dan Total Quality Management (TQM) Dalam Meningkatkan Kinerja Manajerial pada BSI KC Kabanjahe - Paridatul Hikmah; Yusrizal Yusrizal (ITB AAS INDONESIA Surakarta, 2023)
This study aims to analyze the role of information technology, budget participation, and Total Quality Management (TQM) in improving managerial performance at Bank BSI KC Kabanjahe. The research method used in this research is qualitative with a quantitative descriptive approach, where the research technique is carried out using observation techniques, interviews and documentation with the bank and related bank management. The results of the study show that the role of information technology, budget participation, and Total Quality Management (TQM) in improving managerial performance is to positively improve employee and customer performance and facilitate transactions between customers and Bank Syariah Indonesia (BSI) KC Kabanjahe.